Is There a Relation Between Reticular Formation and Storage Symptoms in Men - Zorba, O.U.; Kırbaş, S.; Uzun, H.; Önem, K.; Çetinkaya, M.; Rifaioǧlu, M. (Wiley, 2014)
Objective: To reveal brainstem originated pathology in men with different types of lower urinary tract symptoms blink reflex latency times were assessed. Methods: A total of 32 men, 16 with storage and 16 with voiding symptoms, were enrolled in the study. Blink reflex latency times were analyzed through electrical stimulation of the supraorbital nerve. Two responses in the orbicularis oculi muscle were recorded: the latency times for the early ipsilateral response, R1, and the late bilateral responses, R2. Results: The mean ages of the patients with storage and voiding symptoms were 57.31±6.87 and 58.06±6.29years, respectively. The R2 latency times were significantly longer in men with storage symptoms. However, the R1 latency times were similar for the two groups. Conclusion: Late blink latency times were long only in patients who had storage symptoms. An oligosynaptic path through the trigeminal nuclei, which includes one or two interneurons, is responsible for early response; however, late response is relayed through a polysynaptic path, including neurons in the reticular formation. It has also been shown that stimulation of the pontine reticular formation inhibits the micturition contraction. In some patients, storage symptoms may result from pathology that originates with the reticular formation and this pathology may lead to increases in late blink latency times. Additional studies are needed on other reflexes that are mediated through reticular formation, in order to show the possible dysfunction of the reticular formation in men with storage symptoms. © 2013 Wiley Publishing Asia Pty Ltd.
Keywords: Benign Prostatic Hyperplasia; Blink Reflex; Lower Urinary Tract Symptoms; Pons; Reticular Formation; Storage Symptoms